ANALISIS PENYEBAB BANJIR DI PERUMAHAN SIMALINGKAR, JALAN ROTAN RAYA KECAMATAN MEDAN TUNTUNGAN - Ester Tania Br. Sianturi (Jurnal Samudra Geografi, 2022)
Floods that occur are caused by several factors. The factors are divided into natural factors and human factors. Natural factors such as high rainfall, regional topography, decreased river capacity and others. Natural factors are usually difficult to control, even if they can, it will require quite a large cost. While the Human factor is mainly sourced from the element of population growth where the more people, the higher the need, followed by an increase in infrastructure needs such as roads or sewers, settlements for community residences, clean water facilities, education, and other community services. In addition, population growth will be followed by the need for business land for agriculture, plantations, and industry.